SETL Mathematical Modeling of Early Marriage Dynamics in Wajo Regency - Irwan Irwan; Sitti Aisyah; Maya Sari Wahyuni; Syafruddin Side (Jurusan Matematika FMIPA UNM, 2026)
Early marriage is a social problem that has long-term impacts on the psychological well-being, education, and overall welfare of adolescents in Wajo Regency. This study constructs and analyzes an SETL (Susceptible, Entice, Tied, Liberated) mathematical model to describe the dynamics of early marriage in Wajo Regency. The model consists of a system of differential equations accompanied by equilibrium point analysis, local stability analysis, the basic reproduction number, and numerical simulations. Data were obtained through quantitative questionnaires administered to adolescent respondents. The results show two stable equilibrium points and values of for SMP Negeri 2 Pammana and for SMA Negeri 9 Wajo. The simulation results indicate that the proportion of adolescents tied to early marriage is higher in the senior high school. Although the values for both the junior and senior high schools are below one, they still require intervention due to social and cultural factors that continue to increase adolescents’ vulnerability to early marriage, such as family pressure, limited understanding of the risks associated with early marriage, and restricted access to information and counseling services. These social dynamics surrounding adolescents may sustain or even trigger an increase in early marriage cases if not accompanied by consistent and targeted preventive efforts. This finding underscores the importance of preventive interventions beginning at the elementary education level, with active involvement from families, schools, and relevant institutions in Wajo Regency.